In vitro function of platelets treated with ultraviolet C light for pathogen inactivation: a comparative study with nonirradiated and gamma‐irradiated platelets. Issue 6 (18th December 2014) - Tynngård, Nahreen; Trinks, Marie; Berlin, Gösta
<x xml:space="preserve">Abstract</x> Background During storage of platelet concentrates (PCs) replication of contaminating pathogens might occur, which can be prevented by various pathogen inactivation (PI) methods using photoactive substances in combination with ultraviolet (UV) light. A new method uses only UVC light for PI without photoactive substances. This study evaluates the in vitro function, including hemostatic properties (clot formation and elasticity), of platelets (PLTs) treated with UVC light. Study Design and Methods A PC with 35% plasma and 65% PLT additive solution (SSP+) was prepared from five buffy coats. Three PCs were pooled and divided into 3 units. One unit was used as a nonirradiated control, the second was a gamma‐irradiated control, and the third unit was treated with UVC light. In vitro variables including analysis of coagulation by free oscillation rheometry were analyzed on Days 1, 5, and 7 of storage. Ten units in each group were investigated. Results Swirling was well preserved, and the pH level was higher than the reference limit (6.4) during storage of PLTs in all groups. Glycolysis and PLT activation were higher for UVC‐treated PLTs but the clot‐forming capacity was unaffected. However, immediately after UVC treatment, the clot elastic properties were slightly affected. Hypotonic shock response decreased immediately after UVC treatment but recovered partly during the storage period. Conclusion UVC treatment affected the in vitro properties, but PLT quality and storage stability were well preserved for up to 7 days, and the in vitro hemostatic capacity of UVC‐treated PLTs was only minimally altered. The clinical relevance of these changes needs to be evaluated in controlled trials.